Effect of κ-carrageenan film enriched with limonene extract and curcumin as an indicator of freshness. - Hamdan, S. N. N.; Rovina, K.; Suriati, L.; Pindi, W.; Mantihal, S.; Aris, N.; Roslan, J.; Huda, N. (International Journal of Agricultural Technology, 2025)
This research investigated the creation of κ-carrageenan films incorporating limonene raw extract and curcumin, aiming to serve as effective freshness indicators in food packaging. Fourier Transform Infrared Spectroscopy and Field Emission Scanning Electron Microscopy were employed for film analysis. FTIR spectra indicated the presence of characteristic functional groups including O–H, C–H, C=C, C–O, C–OH, sulphate esters, C=O stretching, and CO–O–SO₃ stretching vibrations. FESEM imaging demonstrated a homogeneous surface with a dense and compact structure. The films’ functional efficacy was assessed using chicken meat as a model system. The addition of curcumin and limonene facilitated observable color alterations corresponding to meat freshness, confirming the film’s utility as a freshness indicator. In addition to indicating spoilage, these natural additives conferred antioxidant and antibacterial properties. The study underscored the potential of biodegradable κ-carrageenan films fortified with natural bioactive compounds as sustainable packaging solutions. However, further research is recommended to optimize limonene and curcumin concentrations and to validate their performance across diverse food matrices, thereby ensuring their commercial viability.